2005
DOI: 10.4319/lo.2005.50.3.0872
|View full text |Cite
|
Sign up to set email alerts
|

A general kinetic model for iron acquisition by eukaryotic phytoplankton

Abstract: The conventional model of iron uptake in marine eukaryotic phytoplankton-the FeЈ model-suggests a dependency of uptake rate on the concentration of unchelated iron species (FeЈ), and not the concentration of total iron or iron chelated with organic ligands. However, iron in seawater is bound by strong organic ligands that buffer such low FeЈ concentrations that they should not support phytoplankton growth. Studies that show uptake and extracellular reduction of siderophore-bound iron by diatoms and provide ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
316
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(328 citation statements)
references
References 36 publications
11
316
1
Order By: Relevance
“…Our data show a similar effect of pH on Fe uptake in the cyanobacterium Trichodesmium. Although the mechanism of Fe uptake by Trichodesmium remains to be fully elucidated, it has been shown that the uptake process can involve a bio-reduction step, as has been demonstrated in some model diatom species (26)(27)(28). Trichodesmium apparently is capable of accessing Fe from Fe oxide, aerial dust, and siderophores (29,30) in which Fe bioavailability should be less sensitive to pH than in our EDTA-buffered medium (4).…”
Section: Discussionmentioning
confidence: 99%
“…Our data show a similar effect of pH on Fe uptake in the cyanobacterium Trichodesmium. Although the mechanism of Fe uptake by Trichodesmium remains to be fully elucidated, it has been shown that the uptake process can involve a bio-reduction step, as has been demonstrated in some model diatom species (26)(27)(28). Trichodesmium apparently is capable of accessing Fe from Fe oxide, aerial dust, and siderophores (29,30) in which Fe bioavailability should be less sensitive to pH than in our EDTA-buffered medium (4).…”
Section: Discussionmentioning
confidence: 99%
“…Remineralisation of particulate Fe at depth mediated by heterotrophic bacteria can also release Fe and ligands , thus potentially affecting Fe bioavailability to primary producers. Moreover, microorganisms can affect Fe redox chemistry, either by direct reduction of an Fe organic complex (often resulting in Fe (II) complexes easier to dissociate; e.g., Shaked et al, 2005) or by the excretion of compounds such as superoxide (Kutska et al, 2005). Despite numerous studies, the parameters controlling the bioavailability of Fe to SO primary producers remains poorly understood (Boyd and Ellwood, 2010;Hassler et al, 2011a).…”
Section: Iron (Fe) Limitationmentioning
confidence: 99%
“…The Fe(II) concentration at the end of the dark period in experiment C was higher than the Fe(II) concentration during irradiance on the previous day. These high Fe(II) concentrations in the dark may be ascribed to two different conceivable mechanisms: reduction of Fe(III) in the dark by either superoxide produced by C. brevis as was shown by Kustka et al (2005) for the diatoms Thallassiosira weissflogii and Thallassiosira pseudonana or by extra-cellular enzymes (Maldonado and Price, 2000;Salmon et al, 2006;Shaked et al, 2005).…”
Section: Day 1 Lights Offmentioning
confidence: 99%
“…Specifically, the Fe redox cycle, as initiated by photochemical processes, is believed to be an important mechanism that converts (colloidal) Fe into more reactive species (defined by the research method applied) resulting in a higher bioavailability for phytoplankton (Finden et al, 1984;Miller and Kester, 1994;. Note, that Fe(II) is suggested to be more bioavailable than Fe(III) (Anderson and Morel, 1980;Anderson and Morel, 1982;Maldonado and Price, 2001;Salmon et al, 2006;Shaked et al, 2005).…”
Section: Introductionmentioning
confidence: 99%